The measurement and interpretation methodology of resistivity logs affected by the Groningen effect – a Polish case study - Baudzis, Stanislaw; Jarzyna, Jadwiga A.; Puskarczyk, Edyta (Geology, Geophysics and Environment, 2020)
True formation resistivity Rt measurement is one of the fundamental logs in the calculation of hydrocarbon resources. That is why it is very important to have the most reliable resistivity data possible. In this paper, the various outcomes obtained by Polish well log analysts and engineers for the proper determination of hydrocarbon saturation in the Main Dolomite deposits in the Polish Lowland are presented. The long history of efforts directed to make proper exploitation decisions in wells where the Groningen effect has been observed is illustrated, starting with the standard measurement and interpretational approach, through the modified construction of a reference electrode in a Laterolog device and ending with an examination of HRLA (High-Resolution Laterolog Array) or Array Compensated Resistivity Tool) ACRt results. The processing of resistivity logs with the special Poprawki software is included.